Electrodeposition of Pr-Mg-Ni ternary alloy films from the choline chloride-urea ionic liquid and their corrosion properties. Issue 5 (13th September 2018) - Li, Miao; Chen, Bi Qing; He, Min; Xiong, Tongtong; Gao, Lixia
Abstract : Purpose: This paper aims to obtain rare earth magnesium alloy with good adhesion and corrosion resistance. Design/methodology/approach: In 353 K oil bath, cyclic voltammetry was used to study the electrochemical behavior of Pr(III), Mg(II) and Ni(II) in choline chloride-urea ionic liquid. The constant potential method was adopted for electrodeposition of Pr-Mg-Ni ternary alloy films. The content of Pr in the Pr-Mg-Ni alloy films changes with respect to the deposition potential, deposition time and concentration ratio of Pr 3+ :Mg 2+ :Ni 2+ . Response surface methodology was applied to optimize the conditions for obtaining high-quality deposition films. Findings: The results showed that the reaction of Ni(II) to Ni is irreversible; this result can be verified by Tafel polarization curve and chronocoulometry curve. Its transfer coefficient on the platinum electrode of 0.32 and diffusion coefficient is 1.0510 −6 cm 2 .s −1 . Mg(II) and Pr(III) cannot solely be reduced to their elemental form, but they can be induced via codeposition by Ni(II). The result shows that under a voltage of −1.00 V, the alloy coating with even structure is obtained when the concentration ratio of Pr 3+ :Mg 2+ :Ni 2+ is 1:1:1 and the deposition time is 20 min. Scanning electron microscopy, X-ray diffraction, energy-dispersive X-ray spectroscopy and other analyses revealed that the alloy coating is amorphous. Polarization curves of the cathode are tested, which manifest the lowest corrosion current density, stating which has good corrosion performance in alkaline solution and NaCl solution; this can be attributed to its dense film structure and good combination with the substrate. Originality/value: It provides some technology for the production of corrosion-resistant materials.